Perforin inhibition protects from lethal endothelial damage during fulminant viral hepatitis. Issue 1 (December 2018) - Welz, M.; Eickhoff, S.; Abdullah, Z.; Trebicka, J.; Gartlan, K.; Spicer, J.; Demetris, A.; Akhlaghi, H.; Anton, M.; Manske, K.; Zehn, D.; Nieswandt, B.; et al.
Abstract CD8 T cells protect the liver against viral infection, but can also cause severe liver damage that may even lead to organ failure. Given the lack of mechanistic insights and specific treatment options in patients with acute fulminant hepatitis, we develop a mouse model reflecting a severe acute virus-induced CD8 T cell-mediated hepatitis. Here we show that antigen-specific CD8 T cells induce liver damage in a perforin-dependent manner, yet liver failure is not caused by effector responses targeting virus-infected hepatocytes alone. Additionally, CD8 T cell mediated elimination of cross-presenting liver sinusoidal endothelial cells causes endothelial damage that leads to a dramatically impaired sinusoidal perfusion and indirectly to hepatocyte death. With the identification of perforin-mediated killing as a critical pathophysiologic mechanism of liver failure and the protective function of a new class of perforin inhibitor, our study opens new potential therapeutic angles for fulminant viral hepatitis. CD8 T cells can protect the liver from viral infection, but can also result in severe liver damage and organ failure. Here, the authors develop a mouse model reflecting fulminant CD8 T cell mediated viral hepatitis, which occurs in a perforin-dependent manner that is protected by the use of perforin inhibitors.